Edges of reality confronting the uncanny. (Lincolnwood, Ill. National Textbook Co., 1999)
Presents five annotated selections of fantastic fiction--"The Sailor-Boy's Tale," "The Canterville Ghost," "Portrait of Jennie," "The Ghostly Rental," and "The Country of the Blind"--along with related articles and discussion questions.
Keywords: Readers (Secondary); Fantasy fiction -- Problems, exercises, etc; Readers -- Fantasy fiction; Readers -- Supernatural; Readers; Supernatural -- Fiction